No evidence of EMAST in whole genome sequencing data from 248 colorectal cancers. Issue 7 (19th February 2021) - Kondelin, Johanna; Martin, Samantha; Katainen, Riku; Renkonen‐Sinisalo, Laura; Lepistö, Anna; Koskensalo, Selja; Böhm, Jan; Mecklin, Jukka‐Pekka; Cajuso, Tatiana; Hänninen, Ulrika A.; Välimäki, Niko; Ravantti, Janne; et al.
Abstract: Microsatellite instability (MSI) is caused by defective DNA mismatch repair (MMR), and manifests as accumulation of small insertions and deletions (indels) in short tandem repeats of the genome. Another form of repeat instability, elevated microsatellite alterations at selected tetranucleotide repeats (EMAST), has been suggested to occur in 50% to 60% of colorectal cancer (CRC), of which approximately one quarter are accounted for by MSI. Unlike for MSI, the criteria for defining EMAST is not consensual. EMAST CRCs have been suggested to form a distinct subset of CRCs that has been linked to a higher tumor stage, chronic inflammation, and poor prognosis. EMAST CRCs not exhibiting MSI have been proposed to show instability of di‐ and trinucleotide repeats in addition to tetranucleotide repeats, but lack instability of mononucleotide repeats. However, previous studies on EMAST have been based on targeted analysis of small sets of marker repeats, often in relatively few samples. To gain insight into tetranucleotide instability on a genome‐wide level, we utilized whole genome sequencing data from 227 microsatellite stable (MSS) CRCs, 18 MSI CRCs, 3 POLE ‐mutated CRCs, and their corresponding normal samples. As expected, we observed tetranucleotide instability in all MSI CRCs, accompanied by instability of mono‐, di‐, and trinucleotide repeats. Among MSS CRCs, some tumors displayed more microsatellite mutations than others as a continuum, and no distinct subset of tumors with the previously proposed molecular characters of EMAST could be observed. Our results suggest that tetranucleotide repeat mutations in non‐MSI CRCs represent stochastic mutation events rather than define a distinct CRC subclass.